PERFORMANCE EVALUATION OF CEMENT MORTAR CONTAINING CONSTRUCTION AND DEMOLITION WASTE AS SUPPLEMENTARY CEMENT MATERIALS - Imane Raini; Laila Mesrar; Touache Abdelhamid; Raini Imad; Jabrane Raouf (Ceramics-Silikáty, 2022)

(untitled)
The purpose of this study is to investigate the effect of fine powders from construction and demolition waste (CDW) as a replacement for cement on the properties of fresh and hardened cement paste and mortar. Specifically, the study focuses on three types of waste powders (WPs) which are: waste brick powder (WBP), waste concrete powder (WCP) and mixed waste powder (MWP). Each type of WP is used to replace 0% to 15% of cement. First, the milled powders are assessed in terms of their morphology (SEM) and composition (X-ray diffraction (XRD) and X-ray fluorescence (XRF)). Such an assessment is carried out based on consistency and setting time tests in order to examine the fresh behaviour of the cement pastes. Second, the mechanical properties, mineralogical and microstructural characteristics are evaluated in order to elucidate the effect of various WPs on the mortar samples. The results demonstrate that, according to the required standards, the use of each WP up to 15% does not alter the mechanical properties of the cement mortar. However, the use of 5% and 10% WBP replacement levels was adequate for improving the strength. Thus, a 52.9 MPa maximum strength was achieved with this mix. Furthermore, the microstructure analyses indicate that the WBP and WMP show a denser mortar structure compared to the reference one. Consistent with the microstructural analyses, the mineralogy analysis reveals that the WBP and MWP have a significant impact on the hydration products of the elaborated mortars.